Computational color imaging : 6th International Workshop, CCIW 2017, Milan, Italy, March 29-31, 2017, Proceedings /: 6th International Workshop, CCIW 2017, Milan, Italy, March 29-31, 2017, Proceedings. (2017) - Unknown
No abstract available